Microporous Polymers from a Carbazole‐Based Triptycene Monomer: Synthesis and Their Applications for Gas Uptake. Issue 2 (26th November 2015) - Zhai, Tian‐Long; Tan, Liangxiao; Luo, Yi; Liu, Jun‐Min; Tan, Bien; Yang, Xiang‐Liang; Xu, Hui‐Bi; Zhang, Chun
Abstract: Two kinds of novel organic microporous polymersTCP s (TCP‐A andTCP‐B ) were prepared by two cost‐effective synthetic strategies from the monomer of tricarbazolyltriptycene (TCT ). Their structure and properties were characterized by FT‐IR, solid 13 C NMR, powder XRD, SEM, TEM, and gas absorption measurements.TCP‐B displayed a high surface area (1469 m 2  g −1 ) and excellent H2 storage (1.70 wt % at 1 bar/77 K) and CO2 uptake abilities (16.1 wt % at 1 bar/273 K), which makes it a promising material for potential application in gas storage. Abstract : High surf is present : Two organic microporous polymers (TCP‐A andTCP‐B ) were prepared by two cost‐effective synthetic strategies from the monomer of tricarbazolyltriptycene (TCT ).TCP‐B displayed a high surface area and excellent H2 storage and CO2 uptake abilities.